Performance of Jatropha Oil-based Biodiesel Fuel in a Single-cylinder Four-Stroke Diesel Engine - H.H Win (ASEAN Journal on Science and Technology for Development, 2012)
Studies on alternative fuels have been active in Myanmar because the rapid mechanization of the agricultural sector demands higher diesel consumption. Jatropha oil-based biodiesel is one of the potential alternatives because of the relative ease of growing and producing this plant. In this study, both the experimental and theoretical analyses of Jatropha oil-based B20 biodiesel wereperformed and compared with conventional diesel. First, B20 was prepared by the base-catalyzed transesterification of the oil and its properties were measured. Second, separate performance tests were conducted on diesel and the biodiesel fuel using a LEYER-16 diesel engine. The speed range of interest was between 1000 r.p.m and 2000 r.p.m. Third, performance simulations were done in MATLAB using an algorithm written based on the theory of the engine operating cycle and air/ fuel compositions. Both experimental and simulation results show that there were no significant differences in the brake power and thermal efficiency of the engine between using diesel and the B20 diesel. However, fuel consumption when using B20 was slightly higher than that of diesel. This difference was marginal and it can be concluded that engine performance characteristics are the same for both diesel and B20 suggesting that B20 has great potential to be used as a substitute for diesel.